Bali Tourism Destination Structural Loyalty Model from Consumer Behavior Perspective - et. al., Christimulia Purnama Trimurti , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is confirmatory research of the destination development model from the perspective of travel motivation which is expected to be used as a theoretical reference model of a tourism marketing mix specifically related to travel motivation, destination image, tourist satisfaction, and tourist loyalty. This research uses a quantitative approach to analyze the direct relationship between the variables that exist in the model. The number of respondents was determined based on the accidental ideal sample size of the SEM-AMOS structural analysis tool around 413 respondents for the domestic tourists and foreign tourists. The conclusion is tourist expectation has a positive and significant effect on destination attractiveness. Destination attractiveness has a positive and significant effect on destination image. Destination image has a positive and significant effect on tourist satisfaction. Tourist satisfaction has a positive and significant effect on tourist loyalty. The implications of this research are maintaining the tourist satisfaction with the existing tourist attractions and their experiences. They are also satisfied with the availability of facilities and services during a vacation in Bali.